Diagnóstico da erosão laminar na alta e média bacia do rio Paraopeba - Daniel Santana Lanza (2011)
This study presents the assessment and mapping of sheet erosion risk in the upper-middle Paraopeba watershed through cartographic modeling. The methodological approach is based on the universal soil loss equation (USLE), an empirical model developed from soil and water loss data. The main physical and antrhopic factors involved in the process of sheet erosion are contained in its formulation. A geographic information system (GIS) was used for its implementation. The physical factors are multiplied to obtain the natural erosion potential (PNE), which is the erosion vulnerability disregarding any vegetation cover or anthropogenic interference. The actual erosion potential (Ea) was obtained through the inclusion of the land use and land cover (LULC) layer in the model. The LULC map was generated based on the classification of ASTER imagery and visual interpretation of high resolution images. Results indicate that over 60% of the study area has strong to very strong PNE. With respect to Ea, more than 54% of the basin suffers soil losses above the average limit of tolerance for soils in Brazil. The study area is 5018 km² and is part of the Paraopeba river basin, located in the upper São Francisco characterized by a predominance of morphogenetic processes and presents a large amount of erosion features. The identification and analysis of accelerated erosion areas can be used for support soil and water conservation in the Paraopeba São Francisco basins.